2003
DOI: 10.1017/s0033583504003956
|View full text |Cite
|
Sign up to set email alerts
|

Geometry of the DNA strands within the RecA nucleofilament: role in homologous recombination

Abstract: Homologous recombination consists of exchanging DNA strands of identical or almost identical sequence. This process is important for both DNA repair and DNA segregation. In prokaryotes, it involves the formation of long helical filaments of the RecA protein on DNA. These filaments incorporate double-stranded DNA from the cell's genetic material, recognize sequence homology and promote strand exchange between the two DNA segments. DNA processing by these nucleofilaments is characterized by large amplitude defor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
41
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 43 publications
(44 citation statements)
references
References 113 publications
3
41
0
Order By: Relevance
“…Thus, transposition will predominantly affect certain areas of the phytoplasma genomes, and hence, the synteny in the rest of the genome can be maintained. Second, because of the absence of recA, ruvA, and ruvB, rearrangements between PMUs through homologous recombination are likely to occur at lower frequencies than in genomes with RecA-dependent homologous recombination machineries (78,79).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, transposition will predominantly affect certain areas of the phytoplasma genomes, and hence, the synteny in the rest of the genome can be maintained. Second, because of the absence of recA, ruvA, and ruvB, rearrangements between PMUs through homologous recombination are likely to occur at lower frequencies than in genomes with RecA-dependent homologous recombination machineries (78,79).…”
Section: Discussionmentioning
confidence: 99%
“…Many research groups have shown that if a force of approximately 65 pN is applied to the ends of a long dsDNA, the molecule will undergo an abrupt overstretching transition into a structure having a length-per-base pair that is approximately 1.7 times the length of B-DNA (1)(2)(3)(4)(5)(6)(7)(8)(9)(10). It has been proposed that the structure of overstretched DNA plays an important role in the function of proteins whose interaction with dsDNA involves a change in length (11)(12)(13)(14).…”
mentioning
confidence: 99%
“…In eukaryotes, from yeast to human, Rad51 is involved in homology search and DNA strand-exchange, central processes for recombination (1,2). The mechanism of DNA strand-exchange appears evolutionarily conserved (3), and has been extensively studied with the bacterial RecA as a model protein (4)(5)(6)(7)(8). The nucleo-protein filament structures appear similar among the RecA and RecA-like proteins, including Rad51 (3,9,10).…”
mentioning
confidence: 99%